2022
DOI: 10.3390/genes13081486
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Suitable Reference Genes for Gene Expression Normalization Studies in Dendrobium huoshanense

Abstract: Dendrobium huoshanense is a kind of precious herb with important medicinal and edible value in China, which is widely used in traditional Chinese medicine for various diseases. Recent studies have paid close attention to the genetic expression of the biosynthetic pathway of the main active components (polysaccharides, alkaloids, and flavonoids), and real-time polymerase chain reaction (qPCR) is one of the most widely used methods for doing so. However, so far, no reference gene selections have been reported in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…In addition, we compared the expression levels of AtACT2 (Arabidopsis) with those of ACT7 and the stable reference genes RPL27 and RPS15 (C. burmnnii) under the Nacl-treated samples (Figure S3), showing that the stability of At-ACT2 was relatively lower. Based on the previous research, TATA-box, as the first promoter found in eukaryotes, was more suitable for q−PCR analysis in a variety of species, such as in Monomorium pharaonic [1], Gleditsia microphylla [56] and Dendrobium huoshanense [57], but in our study it was not the optimum reference gene for some experimental conditions. In addition, eIF-5A was just the best reference gene in different borneol clones and EF1α was the optimum gene for studying different tissues.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, we compared the expression levels of AtACT2 (Arabidopsis) with those of ACT7 and the stable reference genes RPL27 and RPS15 (C. burmnnii) under the Nacl-treated samples (Figure S3), showing that the stability of At-ACT2 was relatively lower. Based on the previous research, TATA-box, as the first promoter found in eukaryotes, was more suitable for q−PCR analysis in a variety of species, such as in Monomorium pharaonic [1], Gleditsia microphylla [56] and Dendrobium huoshanense [57], but in our study it was not the optimum reference gene for some experimental conditions. In addition, eIF-5A was just the best reference gene in different borneol clones and EF1α was the optimum gene for studying different tissues.…”
Section: Discussionmentioning
confidence: 72%
“…These results agreed with previous studies conducted on Momordica charantia [22] and Psoralea corylifolia [21], where TIP41 also demonstrated high stability. However, in studies on Angelica decursiva [17] and Dendrobium huoshanense [44], TIP41 was not identified as the most stable gene, further highlighting the absence of a universal reference gene that is stably expressed across different conditions or organisms. Hence, it is essential to verify presumed reference genes before each RT-qPCR analysis to ensure their suitability for specific experimental conditions.…”
Section: Discussionmentioning
confidence: 97%
“…These primers were synthesized by Sangon Biotech (Sangon, Shanghai, China). The 2 −ΔΔCT method was used for relative quantitative analysis of the data, and the internal reference gene TATA box binding protein-like ( TBP ) [ 35 ] and SYBR Premix Ex Taq II (Novoprotein, Shanghai, China) were employed to validate the DEG expression results. Three biological and three technical replicates of each reaction were analyzed on a LightCycler ® 480 instrument (Roche, Switzerland) with a first step of 95 °C for 5 min for pre-denaturation, followed by 40 cycles of 95 °C for 10 s for denaturation, and 60 °C for 30 s for annealing/extension [ 35 ].…”
Section: Methodsmentioning
confidence: 99%